Origin and Function of Structural Diversity in the Plant Specialized Metabolome - Sandrien Desmet; Kris Morreel; Rebecca Dauwe (Plants, 2021)
The plant specialized metabolome consists of a multitude of structurally and functionally diverse metabolites, variable from species to species. The specialized metabolites play roles in the response to environmental changes and abiotic or biotic stresses, as well as in plant growth and development. At its basis, the specialized metabolism is built of four major pathways, each starting from a few distinct primary metabolism precursors, and leading to distinct basic carbon skeleton core structures: polyketides and fatty acid derivatives, terpenoids, alkaloids, and phenolics. Structural diversity in specialized metabolism, however, expands exponentially with each subsequent modification. We review here the major sources of structural variety and question if a specific role can be attributed to each distinct structure. We focus on the influences that various core structures and modifications have on flavonoid antioxidant activity and on the diversity generated by oxidative coupling reactions. We suggest that many oxidative coupling products, triggered by initial radical scavenging, may not have a function in se, but could potentially be enzymatically recycled to effective antioxidants. We further discuss the wide structural variety created by multiple decorations (glycosylations, acylations, prenylations), the formation of high-molecular weight conjugates and polyesters, and the plasticity of the specialized metabolism. We draw attention to the need for untargeted methods to identify the complex, multiply decorated and conjugated compounds, in order to study the functioning of the plant specialized metabolome.